ANALYSIS OF OPEN SOURCE MFA SOLUTIONS - Ali, Altynai; Toybek , Nurtas; Niyazbek , Nurai; Alimzhanova , Zhanna (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
This article is devoted to the top 5 open source MFA solutions. Technology is changing rapidly, so we will need to adapt open source MFA solutions. Multi-factor authentication (MFA) is a method and technology used to verify the identity of a user. Users need at least two or more types of credential categories to log in or make transactions. A successful combination of at least two independent credentials is a mandatory requirement for the MFA method. It usually combines one of the following three categories of credentials: What the user knows: password or code phrase What does a person have: security badge, keychain or SIM card 3.What the user means: biometric data such as fingerprints, retina or iris, voice or face recognition. MFA requires the user to provide two or more verification factors to access a resource, such as an app or an online account. MFA requires one or more additional verification criteria in addition to the login and password, which reduces the likelihood of a successful cyber attack. Public code is considered"open source". In addition, open source tools and solutions are safe because the code can be tested and verified by anyone.